Echinophora tenuifolia L. branches phytochemical profile and antiproliferative activity on human cancer cell lines. Issue 18 (16th September 2020) - Marrelli, Mariangela; Pisani, Francesca; Amodeo, Valentina; Duez, Pierre; Conforti, Filomena
Abstract: The methanolic extract of Echinophora tenuifolia L. branches and its fractions were evaluated for their in vitro cell growth inhibitory activity on different human cancer cell lines (C32, LoVo and SKBr3) and the normal BJ fibroblasts. All tested samples were effective against the melanoma cell line C32, with IC50 values ranging from 22.8 ± 0.8 to 78.7 ± 1.2 μg/mL, the antiproliferative activity of the dichloromethane fraction being significantly higher. This fraction was also effective against the LoVo adenocarcinoma cell line, with an IC50 value of 53.0 ± 2.1 μg/mL. The ethyl acetate and dichloromethane fractions showed the highest lipid peroxidation inhibitory activity, verified by means of the β-carotene bleaching test. The phytochemical profiles of E. tenuifolia branches extract were established by means of GC-MS and HPTLC. Overall, branches of E. tenuifolia L. could represent a rich source of bioactive compounds, potentially useful in the pharmaceutical field. Graphical Abstract: